2019
DOI: 10.1002/csr.1785
|View full text |Cite
|
Sign up to set email alerts
|

Innovation for sustainable development in the food industry: Retro and forward‐looking innovation approaches to improve quality and healthiness

Abstract: Sustainable development in the food industry requires companies to be more innovative with their products and supply chain as a strategy for developing healthier and higher quality food products, and achieving better economic, environmental, and social performance. A clear path to follow when companies decide to develop innovations for sustainability is still lacking, especially with a focus on quality and healthiness. This study analyzes six case studies in the food industry in Italy, identifying two innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 46 publications
0
27
0
1
Order By: Relevance
“…While we found several pieces of evidence of SBMs in sectors like food (Leon‐Bravo, Moretto, Cagliano, & Caniato, 2019), hospitality (Manaktola & Jauhari, 2007), manufacturing production (Garetti & Taisch, 2012), and public services (Powell & Osborne, 2020) little has been done in other more traditional fields, such as that of insurance. SBMs experiences in the insurance sector include the use of big data analytics to reduce costs in healthcare (Nayak, Bhattacharyya, & Krishnamoorthy, 2019), the introduction of more sustainable managerial practices (Ho, Huang, & Ou, 2018; Lock & Seele, 2015), and the assessment of a sustainable supply chain (Tsvetkova, Yurieva, Karpova, & Khuzhamov, 2019).…”
Section: Literature Review and Research Questionmentioning
confidence: 82%
“…While we found several pieces of evidence of SBMs in sectors like food (Leon‐Bravo, Moretto, Cagliano, & Caniato, 2019), hospitality (Manaktola & Jauhari, 2007), manufacturing production (Garetti & Taisch, 2012), and public services (Powell & Osborne, 2020) little has been done in other more traditional fields, such as that of insurance. SBMs experiences in the insurance sector include the use of big data analytics to reduce costs in healthcare (Nayak, Bhattacharyya, & Krishnamoorthy, 2019), the introduction of more sustainable managerial practices (Ho, Huang, & Ou, 2018; Lock & Seele, 2015), and the assessment of a sustainable supply chain (Tsvetkova, Yurieva, Karpova, & Khuzhamov, 2019).…”
Section: Literature Review and Research Questionmentioning
confidence: 82%
“…McWilliams and Siegel (2001) and León‐Bravo et al (2019) showed that consumer‐oriented CSR includes intangible attributes, such as reputation for quality and trustworthiness. Indeed, as previously mentioned, quality has been shown to be a vital dimension of food companies' CSR; this can, reasonably, be extended to agrifood companies (Calveras & Ganuza, 2018; Kapelko et al, 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…For the specific case of this study, as noted by McWilliams and Siegel (2001), foods are experience goods, that is, their quality, flavor, and even their safety is unknown until they have been consumed (Caswell & Mojduszka, 1996; Caswell & Padberg, 1992). Taking into account that quality and health standards are key strategic elements for agrifood companies (Calveras & Ganuza, 2018; Castilla‐Polo et al, 2018; Chkanikova & Mont, 2015; Kapelko et al, 2020; León‐Bravo et al, 2019) and that there is, according to Brown and Dacin (1997), a direct relationship between CSR and individuals' evaluations of organizations, where entities carry out CSR strategies they can acquire reputations for reliability and honesty, which, in turn, may make consumers relate these intangible company attributes to the quality of their products (Lin et al, 2019; McWilliams & Siegel, 2001; Sánchez‐Vega et al, 2019). The perception that a company possesses socially responsible attributes will create for it a reputation that it is honest and societally aware and, thereby, inspire confidence in the safety and quality of its products (McWilliams & Siegel, 2001; Sánchez‐Vega et al, 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…With a similar aim, León‐Bravo, Moretto, Cagliano, and Caniato () aim to define approaches through which firms can target sustainability performance, specifically improving the quality and healthiness of their products. The study is conducted adopting a multiple case study methodology involving six Italian companies in the food industry.…”
Section: Papers In This Special Issuementioning
confidence: 99%